2022
DOI: 10.1158/1541-7786.mcr-21-0374
|View full text |Cite
|
Sign up to set email alerts
|

MIRO2 Regulates Prostate Cancer Cell Growth via GCN1-Dependent Stress Signaling

Abstract: There is a continued need to identify novel therapeutic targets to prevent the mortality associated with prostate cancer. In this context, Mitochondrial Rho GTPase 2 (MIRO2) mRNA was upregulated in metastatic prostate cancer compared to localized tumors, and higher MIRO2 levels were correlated with poor patient survival. Using human cell lines that represent androgen-independent or -sensitive prostate cancer, we showed that MIRO2 depletion impaired cell growth, colony formation and tumor growth in mice. Networ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…Ye et al [ 7 ] observed increases in both the total amount of GCN2 and phosphorylated GCN2 in colon, lung, breast and liver cancer tissue samples when compared with healthy tissue. Wang et al [ 20 ] made similar observations in human oral squamous cell carcinoma, and, most recently, Furnish et al [ 21 ] observed similar results in a prostate cancer study. In addition to this, a systematic quantified study determined that increased GCN2 expression levels in human papillary renal cell carcinoma were a powerful indicator of poor patient outcomes [ 22 ].…”
Section: Gcn2 Activation In Cancermentioning
confidence: 58%
See 1 more Smart Citation
“…Ye et al [ 7 ] observed increases in both the total amount of GCN2 and phosphorylated GCN2 in colon, lung, breast and liver cancer tissue samples when compared with healthy tissue. Wang et al [ 20 ] made similar observations in human oral squamous cell carcinoma, and, most recently, Furnish et al [ 21 ] observed similar results in a prostate cancer study. In addition to this, a systematic quantified study determined that increased GCN2 expression levels in human papillary renal cell carcinoma were a powerful indicator of poor patient outcomes [ 22 ].…”
Section: Gcn2 Activation In Cancermentioning
confidence: 58%
“…It may be that the role of GCN1 in facilitating ribosomal recycling may explain the more dramatic phenotype of its loss. Furthermore, a recent study implicated GCN2 activity as a sensor of ribosomal fitness [ 21 ]. This study focused on mitochondrial Rho GTPase 2 ( MIRO2 ) — a prognostic marker for metastatic prostate cancer and found that MIRO2 interacted directly with GCN1 and this interaction facilitated GCN2 kinase signalling and ATF4 activation.…”
Section: Potential Roles Of Gcn1 and Gcn20mentioning
confidence: 99%
“…Interestingly, SMAD4 protein, a tumor-suppressor involved in TGFβ signaling, has been shown to be negatively regulated by Miro1 expression ( Li Q. et al, 2015 ). Similarly, Miro2 expression was found to be significantly higher in several types of tumors compared to normal tissue and was upregulated in metastatic cancer cells when compared to primary tumors ( Caino et al, 2016 ; Furnish et al, 2022 ). Downregulation of Miro1 expression was found to regulate negatively tumor cell invasion in syntaphilin knock-down cancer cells ( Caino et al, 2016 ).…”
Section: The Role Of Miro Proteins In Cell Migration and Cancer Metas...mentioning
confidence: 94%
“…However, relevant functional studies are missing. Several studies have shown a link between increased expression of Miro1 and Miro2 and cell migration or metastasis ( Li Q. et al, 2015 ; Caino et al, 2016 ; Furnish et al, 2022 ) . Expression of Miro1 was significantly higher in pancreatic ductal epithelial cells of pancreatic cancer from patients comparing to pre-cancerous tissues, and knock-down of Miro1 in SW1990 pancreatic adenocarcinoma cell line resulted in inhibition of cell migration ( Li Q. et al, 2015 ).…”
Section: The Role Of Miro Proteins In Cell Migration and Cancer Metas...mentioning
confidence: 99%
“…The function of these proteins has been most studied in neurons but has also been characterized in other cell types (Desai et al 2013 ). Dysfunction of Miro1 in neurons has been linked to neurodegeneration (Panchal and Tiwari 2021 ), while more recently, Miro2 was found to have additional roles in the progression of prostate cancer (Furnish et al 2022 ).…”
Section: Biological Contextmentioning
confidence: 99%